Evolving Policy Initiatives for Effective Vocational Technical Education in North Central Zone, Nigeria - Ombugus, Danjuma A.; Angbre, Francis Adams (Asian Journal of Education and Training, 2015)
The study focused on evolving policy initiatives for effective Vocational Technical Education (VTE) on sustainable development. The study adopted a descriptive survey research design and was carried out in North Central Geopolitical Zone of Nigeria. The population for the study was 450 respondents (VTE teachers/lecturers, government officials, industrialists, and community members). Twenty one Policy Initiative items questionnaire were developed, validated and utilized to collect data for the study. Cronbach Alpha method was used in determining the internal consistency of the questionnaire items. The reliability of the items revealed coefficient of 0.82. The study found out that 21 items were regarded as major purposes / objectives of vocational technical education and were rated as initiatives for policy formulation. It was found out that there were no significant differences in the mean rating of the respondents at 0.05 level of significant. It was recommended that the findings in the study be utilized by government for vocational technical education policy formulation in the North Central Zone of Nigeria.